Well-being of Canadian Veterans during the COVID-19 pandemic: cross-sectional results from the COVID-19 Veteran well-being study. Issue 1 (31st December 2022) - Richardson, J. Don; St Cyr, Kate; Forchuk, Callista; Liu, Jenny J. W.; Plouffe, Rachel A.; Le, Tri; Gargala, Dominic; Deda, Erisa; Soares, Vanessa; Hosseiny, Fardous; Smith, Patrick; Dupuis, Gabrielle; et al.
ABSTRACT: Background: The impacts of the COVID-19 pandemic have disproportionally affected different population groups. Veterans are more likely to have pre-existing mental health conditions compared to the general Canadian population, experience compounded stressors resulting from disruptions to familial, social, and occupational domains, and were faced with changes in health-care delivery (e.g. telehealth). The objectives of this study are to assess (a) the mental health impact of COVID-19 and related life changes on the well-being of Veterans and (b) perceptions of and satisfaction with changes in health-care treatments and delivery during the pandemic. Methods: A total of 1136 Canadian Veterans participated in an online survey. Participants completed questions pertaining to their mental health and well-being, lifestyle changes, and concerns relating to the COVID-19 pandemic, as well as experiences and satisfaction with health-care treatments during the pandemic. Results: Results showed that 55.9% of respondents reported worse mental health functioning compared to before the pandemic. The frequency of probable posttraumatic stress disorder, major depressive disorder, generalized anxiety disorder, alcohol use disorder, and suicidal ideation were 34.2%, 35.3%, 26.8%, 13.0%, and 22.0%, respectively. Between 38.6% and 53.1% of respondents attributed their symptoms as either directly related to or exacerbated by the pandemic. Approximately 18% of respondents reported using telehealth for mental health services during the pandemic, and among those, 72.8% indicated a choice to use telehealth even after the pandemic. Conclusions: This study found that Veterans experienced worsening mental health as a result of the COVID-19 pandemic. The use of telehealth services was widely endorsed by mental health treatment-seeking Veterans who transitioned to virtual care during the pandemic. Our findings have important clinical and programmeadministrator implications, emphasizing the need to reach out to support veterans, especially those with pre-existing mental health conditions and to enhance and maintain virtual care even post-pandemic. HIGHLIGHTS: Over 50% of Veterans reported worse mental health compared to before the pandemic. Probable mental health conditions based on self-reports ranged from 13% to 35%. Nearly 1 in 5 Veterans surveyed reported using telehealth for mental health services during the pandemic.